2014
DOI: 10.1016/j.bbamem.2013.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific requirement of cholesterol in the function of the serotonin1A receptor

Abstract: The serotonin1A receptor is an important member of the G protein-coupled receptor (GPCR) family. It is involved in the generation and modulation of a variety of cognitive and behavioral functions, and serves as a drug target. Previous work from our laboratory has established the sensitivity of the function of the serotonin1A receptor to membrane cholesterol. Solubilization of the hippocampal serotonin1A receptor utilizing the zwitterionic detergent CHAPS is accompanied by loss of cholesterol and results in red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 79 publications
3
60
0
Order By: Relevance
“…An important aspect of our results is that the interaction between cholesterol and the serotonin1A receptor appears to be stringent, since immediate biosynthetic precursors of cholesterol (differing with cholesterol merely in a double bond) were not able to maintain receptor function (Paila et al, 2008;Singh et al, 2009). In addition, we recently showed that the requirement of cholesterol for receptor function is diastereospecific, but not enantiospecific (Jafurulla et al, 2014). This difference in sterol stereospecificity for receptor function appears to be related to membrane dipole potential (Bandari et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An important aspect of our results is that the interaction between cholesterol and the serotonin1A receptor appears to be stringent, since immediate biosynthetic precursors of cholesterol (differing with cholesterol merely in a double bond) were not able to maintain receptor function (Paila et al, 2008;Singh et al, 2009). In addition, we recently showed that the requirement of cholesterol for receptor function is diastereospecific, but not enantiospecific (Jafurulla et al, 2014). This difference in sterol stereospecificity for receptor function appears to be related to membrane dipole potential (Bandari et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Native hippocampal membranes were prepared from frozen hippocampal tissue, as described previously (Jafurulla et al, 2014). The final pellet (native membranes) was suspended in a minimum volume of buffer C (50 mM Tris, pH 7.4), homogenized using a hand-held Dounce homogenizer, flash frozen in liquid nitrogen and stored at -80 ºC.…”
Section: Hippocampal Membrane Preparation and Cholesterol Depletionmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane cholesterol has been shown to modulate the function of a number of GPCRs [35,36,[41][42][43][44][66][67][68][69][70][71][72][73][74]. A specific GPCR that has received a lot of attention in terms of cholesterol sensitivity of its organization, dynamics, and function is the serotonin 1A receptor [36,42,43].…”
Section: Cholesterol: a Lipid Intimately Associated With Gpcrsmentioning
confidence: 99%
“…This was demonstrated utilizing a variety of approaches which include (i) physical depletion of membrane cholesterol using the sterol-specific carriers such as methyl--cyclodextrin (M CD) [66,68], (ii) treatment with agents such as nystatin (a polyene antibiotic) [67] and digitonin (a saponin family detergent) [70], which complex cholesterol and modulate the availability of membrane cholesterol without physically depleting it, (iii) enzymatic oxidation of cholesterol to cholestenone by cholesterol oxidase [69], and The results show that the requirement of membrane cholesterol for the serotonin 1A receptor function is diastereospecific but not enantiospecific. Adapted and modified from [35]. See text for more details.…”
Section: Cholesterol: a Lipid Intimately Associated With Gpcrsmentioning
confidence: 99%